Study of Sensitivity Pattern of Metronidazole on Axenic Culture of Entamoeba Histolytica In Vitro (Journal of Dhaka Medical College, 2010)
Objective: To evaluate the sensitivity pattern of metronidazole against Entamoeba histolytica. Design: It was an experimental study. Settings: The study was carried out in Parasitology Laboratory, ICDDR,B Dhaka from January 2007 to June 2007. Subjects: Entamoeba histolytica (Strain: MS 27 5030) Main outcome measure: Minimum inhibitory concentration (MIC). Results: In this study MIC of metronidazole was < 0.08 mg/ml. Conclusion: The result suggests that metronidazole is still the standard drug for treatment of amoebiasis Key words: Axenic culture; Entamoeba histolytica; Metronidazole. DOI: 10.3329/jdmc.v19i1.6256 J Dhaka Med Coll. 2010; 19(1) : 65-66.